2007
DOI: 10.1519/00124278-200705000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Performance Characteristics of Adolescent Club Volleyball Players

Abstract: Melrose, D.R., F.J. Spaniol, M.E. Bohling, and R.A. Bonnette. Physiological and performance characteristics of adolescent club volleyball players. J. Strength Cond. Res. 21(2):481-486. 2007.-The objective of this investigation was to examine the physical and performance characteristics of adolescent club volleyball players. Twenty-nine adolescent girls, aged 12 to 17 years (14.31 Ϯ 1.37) were participants in this investigation. All athletes were members of a competitive volleyball club. The following group val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 10 publications
1
30
0
4
Order By: Relevance
“…In addition to the computer-aided assessment, the alignement of head, shoulders, abdomen (in the sagittal plane), chest arch and alignment of knees were point-rated [10].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the computer-aided assessment, the alignement of head, shoulders, abdomen (in the sagittal plane), chest arch and alignment of knees were point-rated [10].…”
Section: Methodsmentioning
confidence: 99%
“…Diversos estudios han valorado la extensibilidad isquiosural en deportistas, tales como nadadores (Pastor, 2000;Sanz, 2002), corredores de larga distancia (Wang et al, 1993;Trehearn & Buresh, 2009), piragüistas (García-Ibarra et al, 2007;López-Miñarro et al 2008a, 2008b, 2009b, 2010bLópez Miñarro & Alacid, 2010), remeros (Stuchfield & Coleman, 2006), halterófilos (Dillon et al, 2004), gimnastas de rítmica Martínez, 2004), futbolistas (Oberg et al, 1984;McIntyre & Hall, 2005;López-Miñarro et al, 2007a, 2007bCaldwell & Peters, 2009;Henderson et al), jugadores de fútbol australiano (Young et al, 2005), luchadores (Mirzaei et al, 2009), jugadoras de lacrosse (Enemark-Miller et al, 2009), tenistas (Kibler & Chandler, 2003), taekwondistas (Toskovic et al, 2004), y jugadoras de voleibol (Melrose et al, 2007). La mayoría de estos estudios encuentran una extensibilidad reducida, excepto en aquellos deportes donde la misma tiene un papel muy importante en la ejecución de los gestos téc-nicos, como en la gimnasia rítmica y la danza.…”
Section: Introductionunclassified
“…Vertical jump is of the utmost importance in volleyball and is mainly used during serving, setting, attacks and blocks, which are essential for scoring a point. Studies investigating the morphofunctional characteristics of volleyball players have focused on vertical jump height 5,11,[17][18][19][20][21][22] , although today the maximum range of attack of the player during jumping and not his vertical jump height has become more important. Marques et al 5 demonstrated the existence of different types of physical fitness and anthropometric profiles in male volleyball as a function of the specific position of the players.…”
Section: Introductionmentioning
confidence: 99%